Virtual chain: A storage model supporting cross‐blockchain transaction. (8th September 2020) - Wang, Yan; Yang, Bingqing; Liu, Jingxin; Zeng, Hui; Xia, Changqing
Summary: At present, blockchain is not only applied in the financial field, but also extended to the medical, insurance, internet of things, and many other fields. Its independence leads to more and more significant problems of network isolation. To address the problem of the cooperative operation between different blockchains, this article proposes virtual chain, a storage model supporting cross‐blockchain transaction. It not only ensures that cross‐chain transactions are tamper‐proof and traceable but also realizes completely decentralized storage. First, to tackle the multidimensional heterogeneous problem existing in cross‐chain trading, a data structure based on prefix tree is proposed to manage cross‐chain trading data on top of source chain and target chain. Second, a signature verification mechanism based on elliptic curve is proposed to meet the operational atomicity requirements of both parties of cross‐chain transaction. Third, the data fusion technology is used to expand the block capacity indirectly to achieve the high throughput of cross‐chain transactions. Finally, by using the credibility‐based access control and block chain technology to ensure the security of the data storage model, and conduct security analysis from three aspects of tamper‐proof, data protection and anti‐conspiracy node attack. The experiment shows that the proposed cross‐chain transaction storage model can realize the efficient storage of the heterogeneous data, and satisfy the high requirement of the cross‐chain transaction. Moreover, the virtual chain storage model establishes a safe and reliable working environment.